Providing Incentives to Improve and Develop the Performance of Teachers - Imam Makruf, Fauzi Muharom, Achmad Buchori, Rita Aryani, Suhendri (International Journal of Advanced Science and Technology, 2020)
The work of a teacher is noble. The daily task of the teacher is to improve the quality of education and direct students to be model students, competent, smart, and noble. It is not easy for a teacher to direct students to become better people. The teacher has a monthly salary that is not so large that the teacher needs additional money so that the teacher’s life is guaranteed and prosperous. Incentives are additional money that will be given to teachers. Not all teachers have the same amount of incentives. Every teacher will get an incentive according to the performance he gets. Decision support systems are needed in determining the number of incentives that will be given to the teacher so that the acceptance of incentives will be more equitable by applying this method, incentives issued by parties who are going to be more optimal and targeted.